Experimental and molecular dynamics study of boron nitride nanotube-reinforced polymethyl methacrylate composites. (January 2020) - Sharma, Sumit; Setia, Prince; Chandra, Rakesh; Thakur, Nitin
Heat dissipation is very essential for the efficient working of electronic devices. There is a widespread demand for high thermal conductivity materials. Boron nitride nanotubes have high thermal conductivity but due to their poor interfacial adhesion with polymers, their use as heat dissipating material is restricted. In this study, a silane-coupling agent has been used to modify the boron nitride nanotubes. These tubes were then inserted in polymethyl methacrylate matrix. Various properties such as thermal conductivity, storage modulus, and loss factor have been predicted. Molecular dynamics simulations have also been used for accurate prediction of the properties of boron nitride nanotubes/polymethyl methacrylate composites. The boron nitride nanotubes weight percentage was varied from 0% to 70% for studying the effect on thermal conductivity, storage modulus, and loss factor. The experimentally obtained thermal conductivity increased rapidly from 0.6 W/mK at 40 wt.% of boron nitride nanotubes to about 3.8 W/mK at 80 wt.% of boron nitride nanotubes in polymethyl methacrylate matrix (an increase of nearly 533%). A similar trend was obtained using molecular dynamics simulations. The storage modulus increased from 2 GPa (for pure polymethyl methacrylate) to about 5 GPa (for 70 wt.% boron nitride nanotubes). The glass transition temperature of boron nitride nanotubes/polymethyl methacrylate composites shifted to higher temperatures with an increase in boron nitride nanotubes weight percentage.